A NEW VIEW OF REALITY (TV SERIES CULTURE STUDIES) - Konstantin Rayhert (Cхід, 2018)
The study examines the combination of the Philip Kindred Dick’s concept definition of reality and the Jakob von Uexküll’s conception of Umwelt in the 2nd episode of the 2nd season of TV series ‘Legion’. The authors of TV series ‘Legion’ propose an unexpected merge of the Philip Kindred Dick’s definition of ‘reality’ and the Jakob von Uexküll’s conception of Umwelt, forcing the researchers to look at reality from the surprising perspective. As a result of the combination, it’s showed that the critical characteristic of the human’s Umwelt is a belief of the human in the authenticity of the reality within which the human exists. The very human’s Umwelt is a merger of the first Nature which is a physical one and the second Nature which is a culture; and at the same time the second Nature consists of physical (realized in the physical artifacts of culture) and virtual (realized in humans minds) dimensions. Human being depends on culture, especially on its virtual part because the very part is responsible for human language, system of signs, values and virtues and, in a certain sense, consciousness and mind, and, therefore, human relations to the external, that is, reality. In that case for human being it is crucial to have the preliminary understanding of what is real and what is not real, because its functioning, as a part of nature and a part of culture, especially society, depends on that understanding. It all attests that those two Natures determine the human’s Umwelt, but if the Philip Kindred Dick’s concept definition of reality is trusted, the authentic reality component part of the human’s Umwelt is only the physically existed ones because only the physically existed ones don’t go away if someone stops believing in them. However, there is always the fraught with danger of the falsified reality by someone who or what has power to fabricate the reality; it can be other people, something that is not people, or you.